Waiting for Breakthrough in Conventional Submarine’s Prime Movers - Lus, Tomasz (Transactions on Maritime Science, 2019)
Submarines, as a very expensive and sophisticated type of weaponry, are being intensively exploited by the armed forces of many countries. This means that submarines are sent ever longer patrols, sometimes to distant regions. To meet such requirements, submarine sub-systems and components must have high reliability and operational readiness indicators. Among the many machines and devices found on submarines, the ones that generate, store, and consume energy (mainly electricity) deserve special attention. The largest energy consumers on the submarine are the components of its propulsion system. One of the most complicated and loaded devices on board submarine is a power generator with a diesel engine driving it, on whose continuous and reliable work the safe performance of tasks depends. According to statistical research, despite its importance for the process of performing tasks by submarines, diesel engines are still the least reliable devices on submarines. Despite the constant technological development of piston engines, their work in very difficult conditions under heavy load and at high counter-pressure at the exhaust outlet promotes their malfunction and damage. From this point of view, the development of charge air systems for submarine diesel engines based on the construction experience of MTU Company is described in the paper. The classification of submarines, their propulsion systems, and the working conditions of engines on submarines are presented in the paper. Air-Independent Propulsion (AIP) systems with their applications on chosen submarines are also described. The most significant change in submarine propulsion system observed in 2018, transition from lead-acid to lithium-ion batteries, is also presented.